Pengaruh Promosi, Harga, dan Kualitas Pelayanan terhadap Kepuasan Konsumen di Toko Simplestore Semarang - Andreas Dewa Kristandy; M. Fathur Rahman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of promotion, price, and service quality on customer satisfaction at Simplestore Semarang. The method used is a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, which is processed through questionnaire data from 100 respondents. The results of the analysis show that service quality has a significant effect on customer satisfaction, while promotion and price do not show a significant effect. The findings confirm that superior service experience is a major factor in shaping customer satisfaction, while promotion and pricing strategies need to be adjusted to be more relevant to consumer needs. This research provides practical implications for retail management in designing strategies to increase customer satisfaction in a more targeted manner.